2003
DOI: 10.1007/s10038-003-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Catalog of 680 variations among eight cytochrome P450 (CYP) genes, nine esterase genes, and two other genes in the Japanese population

Abstract: We screened DNAs from 48 Japanese individuals for single-nucleotide polymorphisms (SNPs) in eight cytochrome P450 (CYP) genes, nine esterase genes, and two other genes by directly sequencing the relevant genomic regions in their entirety except for repetitive elements. This approach identified 607 SNPs and 73 insertion/deletion polymorphisms among the 19 genes examined. Of the 607 SNPs, 284 were identified in CYP genes, 302 in esterase genes, and 21 in the other two genes (GGT1, and TGM1); overall, 37 SNPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…In this report, a 33% overestimation of the frequency of CYP2A6 Ã 4A&D due to CYP2A6 Ã 28A was found. This may be of particular importance in Asian populations because the frequency of CYP2A6 Ã 4 is much higher , the frequency of CYP2A6 Ã 28A is unknown, and the 5750G4C sequence variant (found in CYP2A6 Ã 28A) was first identified in a Japanese population [Saito et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, a 33% overestimation of the frequency of CYP2A6 Ã 4A&D due to CYP2A6 Ã 28A was found. This may be of particular importance in Asian populations because the frequency of CYP2A6 Ã 4 is much higher , the frequency of CYP2A6 Ã 28A is unknown, and the 5750G4C sequence variant (found in CYP2A6 Ã 28A) was first identified in a Japanese population [Saito et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Our primary aim was to characterize four CYP2A6 nonsynonymous sequence variants, namely 594G4C (p.V110L) [Haberl et al, 2005], 1672T4C (p.F118L) [Solus et al, 2004], 2162_2163GC4A (R203frameshift [FS]) [Solus et al, 2004], and 5750G4C (p.E419D) [Saito et al, 2003], with respect to their haplotype, allele frequency, and in vivo functional impact. A secondary aim was to confirm whether established CYP2A6 alleles that have been predominately discovered and characterized in Caucasian and Asian populations have similar pharmacokinetic effects in a population of Black African descent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the regulation mechanisms of human AADAC expression are not fully understood. Saito et al (2003) previously found 23 SNPs in the AADAC gene using DNA samples of 48 Japanese. Among them, only an SNP that was also found in this study (g.13651G Ͼ A, c.931G Ͼ A) leads to an amino acid change (V281I).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the large resemblance between the CES1A1 and CES1A2 promoter sequences, the SNPs on this region (29) are hardly distinguishable. We reported that several SNPs exist exclusively on the promoter regions of CES1A1 or CES1A2, respectively (Yoshimura et al, under submission).…”
Section: Discussionmentioning
confidence: 99%